Sorting on the labour market: A literature overview and theoretical framework - Stephan O. Hornig; Horst Rottmann; Rüdiger Wapler (Hochschule für angewandte Wissenschaften Amberg-Weiden (HAW), 2011)
In the literature there are basically two main approaches that explain the positive link between the level of education and wages: the human-capital theory and the signalling/screening (collectively known as sorting) theory. We highlight the similarity and differences between these theories and present a general theoretical model of screening with productivity-enhancing effects of education from which we derive four empirically testable hypothesis. – – In der Literatur sind zwei Theorien zur Erklärung des positiven Zusammenhangs zwischen dem Bildungsniveau und dem Lohn vorherrschend: die Human Kapital-Theorie und die Signaltheorie. Wir beschreiben die Gemeinsamkeiten und Unterschiede beider Theorien und präsentieren ein allgemeines theoretisches Signal-Modell mit produktivitätserhöhenden Effekten der Bildung. Anhand diesem Modell entwickeln wir vier Hypothesen, die empirisch getestet werden können.
Keywords: J24; J31; 330; human-capital theory; signalling; screening